Sikap Guru Dalam Menghadapi Siswa Yang Berkebutuhan Khusus Di Kelas 2 SDN Jelegong 01 Rancaekek - Yuga Fibra Nurhakim; Yayang Furi Furnamasari (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to find out how the teacher's attitude is in dealing with students with special needs in class 2 at SDN Jelegong 01 Rancaekek. This research was conducted at SDN Jelegong 01 Rancaekek. The method used in this research is descriptive qualitative research. For data collection techniques in this study using classroom observations, interviews with grade 2 teachers, reviewing from literature studies by searching from book, articles, journals, theses, etc. related to the research being conducted. Based on the results of this study it can be concluded that in dealing with grade 2 students with special needs at SDN Jelegong 01 Rancaekek the teacher's attitude is painstaking in providing special treatment according to what the student needs but the teacher also tries so that these students and their families do not feel discriminated against and do not make Other students feel that there is something special in the class.